2018
DOI: 10.1155/2018/2347593
|View full text |Cite
|
Sign up to set email alerts
|

Canaloplasty versus Nonpenetrating Deep Sclerectomy: 2-Year Results and Quality of Life Assessment

Abstract: Purpose To compare phacocanaloplasty (PC) and phaco-non-penetrating deep sclerectomy (PDS). Methods 75 patients with uncontrolled glaucoma and cataract were randomized for PC (37 eyes) or PDS (38 eyes). Intraocular pressure (IOP) and number of medications (meds) were prospectively evaluated. Follow-up examinations were performed on days 1 and 7 and after 1, 3, 6, 12, 18, and 24 months. Surgical success was calculated. Complications and postoperative interventions were noted. Quality of life (QoL) was analyzed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…In another study, the same group of authors reported on the results of a 24-month comparison between PCP and phaco-DS. In this study 37 eyes were randomized to receive PCP and 38 eyes to receive phaco-DS [ 70 ]. Quality of life (QoL) was evaluated by the means of the National Eye Institute Visual Function Questionnaire-25 items (NEI-VFQ-25).…”
Section: Comparison With Other Non-penetrating Surgeriesmentioning
confidence: 99%
“…In another study, the same group of authors reported on the results of a 24-month comparison between PCP and phaco-DS. In this study 37 eyes were randomized to receive PCP and 38 eyes to receive phaco-DS [ 70 ]. Quality of life (QoL) was evaluated by the means of the National Eye Institute Visual Function Questionnaire-25 items (NEI-VFQ-25).…”
Section: Comparison With Other Non-penetrating Surgeriesmentioning
confidence: 99%
“…This paper represents further aspects of a previously published study, where patients and methods were described in detail 5 , 11 . The methods and results are presented in line with Guidelines on Design & Reporting Glaucoma Trials 12 .…”
Section: Methodsmentioning
confidence: 99%
“…In the course of the study the intraocular pressure (IOP), the number of antiglaucoma medications, Best Corrected Visual Acuity (BCVA), autokeratorefractometry (AKR), Humphrey 24-2 visual fields (VF), Optical Coherent Tomography (OCT) morphology of the surgical site, Quality of life (QoL) assessment- were collected prospectively 5 , 11 .…”
Section: Methodsmentioning
confidence: 99%
“…This paper represents further aspects of a previously published study, where patients and methods were described in detail 5,11 Patients with coexisting glaucoma and cataract (NC1 and NC2) classi ed according to the LOCS III scale were quali ed for the study.…”
Section: Subjectsmentioning
confidence: 99%
“…In the course of the study the IOP, the number of antiglaucoma medications, BCVA, AKR, VF, OCT morphology of the surgical site, QoL assessment-were collected prospectively 5,11 .…”
Section: Designmentioning
confidence: 99%